Excavating CBC’s Docudrama The Tar Sands - McCurdy, Patrick (Imaginations)

(untitled) (York University, 2022)
This article examines the political controversy around the banned 1977 CBC docudrama _The Tar Sands_, which portrays the personal and political struggle of Alberta Premier Peter Lougheed to secure the Syncrude agreement to develop Alberta’s bitumen sands. Immediately following the docudrama’s broadcast, Lougheed launched a lawsuit which ultimately resulted in the show’s expulsion from CBC archives. While the CBC docudrama sought to dramatize and elevate political critiques of the tar sands, Lougheed’s litigious reaction quickly buried them, obfuscating the real possibility that The Tar Sands—while a work of fiction—portrays the genesis of Alberta’s corporate capture by foreign oil.